RISK OF LANGUAGE DELAY IN TODDLERS WITH PROLONGED SCREEN TIME : EVIDENCE BASED CASE REPOR - Muhammad Sobri Maulana (JECIES: Journal of Early Childhood Islamic Education Study, 2020)
Background: Language development of children starts early in infantcy and surges in 2 years of life, updated knowledge about association of language delay with its aggravating risk factor, in this case prolong sreening time, is very important to determine the prognosis of language development in children. Objective: To investigate the association between increased risk of language delay in toddlers with prolonged screen time. Methods: All included studies were collected from Pubmed, Scopus, EBSCO, Clinical Key and Science Direct on February 11th  2020. These articles were then critically appraised using standard Oxford criteria of Evidence Based Medicine prognostic checklist. Result: Two eligible retrospective cohort studies from Lin et al (2014) and Byeon and Hong (2015) are included in this EBCR. Both were calculating the risk of language delay in toddlers between 15-35 months and 24-30 months exposed to screen viewing. Toddlers with more than 2 hours of watching television have higher risk of language delay (Odds Ratio: 3.3 (95%CI 1.5-7.3) and 2.74 (95%CI 1.13-6.65) respectively). Conclusion : The risk of language delay in toddlers is confirmed to be proportionately increased with the increases of screen duration. Maximum language development may be achieved by giving more two-way communication opportunities other than screen viewing.Keywords: Language delay, Toddlers, Screen time. ABSTRAKLatar belakang : Perkembangan bahasa anak-anak dimulai sejak kanak-kanak dan melonjak dalam dua tahun awal kehidupan, pengetahuan terbaru tentang hubungan antara keterlambatan bahasa dengan faktor risiko yang memburuk, dalam hal ini memperpanjang waktu menonton televisi sangat penting untuk menentukan prognosis perkembangan bahasa pada anak-anak. Tujuan : Untuk menyelidiki hubungan antara peningkatan risiko keterlambatan bahasa pada balita dengan  waktu menonton televisi yang lama. Metode : Semua studi literatur yang dimasukkan dan dikumpulkan dari Pubmed, Scopus, EBSCO, Clinical Key dan Science direct pada 11 Februari 2020. Jurnal-jurnal ini kemudian di nilai secara appraisal menggunakan kriteria standar Oxford dalam kaidah laporan kasus berbasis bukti. Hasil : Dua studi kohort retrospektif yang memenuhi syarat kaidah laporan kasus berbasis bukti / EBCR yaitu Lin et al (2014) dan Byeon dan Hong (2015) dimasukkan dalam EBCR ini. Keduanya melakukan penelitian dan menghitung risiko keterlambatan bahasa pada balita usia antara 15-35 bulan dan 24-30 bulan yang terpapar menonton televisi dalam waktu lama . Balita yang menonton televise lebih dari dua jam sehari memiliki risiko keterlambatan bahasa yang lebih tinggi masing-masing(Odds Ratio: 3.3 (95%CI 1.5-7.3) dan 2.74 (95%CI 1.13-6.65). Kesimpulan : Risiko keterlambatan bahasa pada balita dipastikan akan meningkat secara proporsional dengan meningkatnya durasi menonton televise. Perkembangan bahasa pada anak lebih maksimal dapat dicapai dengan memberikan lebih banyak waktu untuk berkomunikasi dua arah antara keluarga selain dari menonton televisi.